Determinant Factors of Drainage Infrastructure Project Success in Simpang Sanur–Tohpati Area, Denpasar City - Kumara, I Nyoman Indra; Harefa, Pandu Sambuaga; Tapa, I Gede Fery Surya; Pancane, I Wayan Dikse; Indrashwara, Decky Cipta; Putri, Dewa Ayu Putu Adhiya Garini (Journal of Civil Engineering and Planning (JCEP), 2025)
The city of Denpasar has experienced rapid urbanization, necessitating improvements in infrastructure. One such infrastructure project is located in the Simpang Sanur–Tohpati area of Denpasar City. The success of this drainage project is crucial in addressing the recurring flood problems that threaten the city annually. This study aims to analyze the key determinants of project success in the drainage management initiative in the Simpang Sanur–Tohpati area. A quantitative approach was employed, using multiple linear regression analysis to examine the relationship between independent variables and the dependent variable. Primary data were collected through questionnaires distributed to respondents from the Denpasar City Government, contractors, and consultants directly involved in the implementation of the project. The findings indicate that cost, time, quality, and occupational health and safety (OHS) have a significant influence on project success. Notably, the study highlights the need to pay particular attention to OHS implementation, even though its statistical contribution is relatively smaller compared to the other factors. This research contributes to a better understanding among stakeholders of the importance of each factor in determining project success. It underscores the need for thorough project planning, emphasizing that cost, time, quality, and the implementation of OHS are critical factors that significantly influence the success of future projects.